Smartphone Addiction and Sleep Disorder among Students at SDN Setonorejo 1 Kras Kediri - Erva Elli Kristanti (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Addiction is a initial habit that is always done without self-control. Addiction according to the KBBI is a physical and mental addiction or dependence on a substance. The bad effects of internet addiction are concentration problems, sleep pattern disturbances that can have a bad impact on performance. The objective of this study was to identify the description of Smartphone Addiction at State Elementary Setonorejo Kras Kediri. The research method used was descriptive. Data retrieval was carried out using the Chen Internet Addictional Scale (CIAS) to obtain smartphone incident data. The number of research respondents were 27 students at State Elementary Setonorejo Kras Kediri. Based on the results of the study, it was found that most of the students of State Elementary Setonorejo Kras Kediri did not experience Smartphone Addiction as many as 20 students (74.07%) but there were students who were at risk of experiencing Smartphone Addiction as many as 7 students (28.93%). Meanwhile, disturbances in initiating sleep did not occur at State Elementary Setonorejo Kras Kediri as many as 27 (100%). Based on these results, it was necessary for the cooperation of the school and parents to break the level of gadget addiction so that students can continue to achieve achievement Â Â